2021
DOI: 10.3390/genes12111804
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study of a Korean Population Identifies Genetic Susceptibility to Hypertension Based on Sex-Specific Differences

Abstract: Genome-wide association studies have expanded our understanding of the genetic variation of hypertension. Hypertension and blood pressure are influenced by sex-specific differences; therefore, genetic variants may have sex-specific effects on phenotype. To identify the genetic factors influencing the sex-specific differences concerning hypertension, we conducted a heterogeneity analysis of a genome-wide association study (GWAS) on 13,926 samples from a Korean population. Using the Illumina exome chip data of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Mutations in the ATXN2 gene were reported to be associated with susceptibility to type I diabetes, obesity, and hypertension ( Davalos-Rodriguez et al 2022 ). HECTD4 is involved in the metabolic process of glucose and is also associated with susceptibility to hypertension, with rs2074356 showing significant genetic heterogeneity in the systolic blood pressure ( Cho and Jang 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in the ATXN2 gene were reported to be associated with susceptibility to type I diabetes, obesity, and hypertension ( Davalos-Rodriguez et al 2022 ). HECTD4 is involved in the metabolic process of glucose and is also associated with susceptibility to hypertension, with rs2074356 showing significant genetic heterogeneity in the systolic blood pressure ( Cho and Jang 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The newly found rs6990123 showed an outstanding association strength compared to others, and it participated in two-order interactions, as shown in Table 5 , to make top associated pairs with SNPs absent from the list of the top main effects. rs2074356 was reported to have a strong association with γ-GTP levels [ 35 ], and rs11066280 was reported to have a strong association with type 2 diabetes, which is closely related to γ-GTP [ 36 ]. rs12229654, which has been reported to be associated with both γ-GTP and high-density lipoprotein cholesterol [ 37 ], was also found.…”
Section: Resultsmentioning
confidence: 99%
“…[8] Similarly, a recent study showed evidence of heterogeneity of the genetic effects of hypertension-associated variants between males and females and, that the variants leading sex-speci c genetic susceptibility may relate to genes involved in steroid hormone receptor biosynthesis pathway. [9] Alongside studies in human populations, rodent models have been a valuable resource for the better understanding of hypertension and its relation to adiposity. In a recently published study, a hypotensive SPAK T243A/T243A mice also exhibited an obesity-resistant phenotype.…”
Section: Introductionmentioning
confidence: 99%